Iron and Vitamin A Status of Children Aged 0 to 36 Months in Thulamela Municipality, Vhembe District, South Africa - Anzani Mugware; Selekane Ananias Motadi; Alphonce Bere; Lindelani Fhumudzani Mushaphi (MDPI AG, 2024)
Objective: The present study assessed the iron and Vitamin A status of children aged 0 to 36 months in Thulamela municipality, Vhembe District. Methods: A cross-sectional study was conducted among 250 children aged 0 to 36 months attending well-baby clinic services with their mothers. Convenience sampling was used to select study participants, and simple random sampling was used to choose clinics. Data were gathered via a questionnaire administered by the researcher and field workers from August to September 2019. Standard techniques were used to measure body weight and height. In addition, serum retinol, haemoglobin, iron, ferritin, transferrin saturation, and transferrin levels were also assessed. Information on dietary diversity was gathered through a 24 h dietary recall. Results: The prevalence of underweight, wasting, and stunting was 3.6%, 2%, and 9.2%, respectively. Using serum retinol <10 µg/dL, 22% of children had vitamin A deficiency. The prevalence of anaemia was 53.6%, while 13.1% of children had iron deficiency anaemia when using serum ferritin of less than 12 μg/dL. Most children (90.8%) had an inadequate dietary diversity score, while 9.2% had sufficient dietary diversity. The most consumed food groups were grains, roots and tubers, vitamin A rich fruits and vegetable, and flesh foods. A higher percentage (44%) of children with low iron ferritin were underweight compared to those with normal iron ferritin (df = 1, p-value = 0.007). Conclusion: Iron, anaemia, and vitamin A deficiencies, accompanied by a high prevalence of stunting, were common among children in Thulamela Municipality. Thus, improving nutritional status in this area is a critical need.